2018
DOI: 10.3390/su10051657
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction and Loyalty as a Part of Customer-Based Corporate Sustainability in the Sector of Mobile Communications Services

Abstract: In the service sector, the issue of customer satisfaction is being paid great attention. It has become central concern for companies of services to improve service quality, and to maintain customer loyalty within a highly competitive marketplace. The success of customer satisfaction is not only closely related to a company's quality management and marketing activities but it also has significant impacts on the company's future and its customer-based corporate sustainability. Customer satisfaction influences va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 26 publications
2
27
0
8
Order By: Relevance
“…Each of these latent variables is determined by measurable variables (22). This model is based on the use of a questionnaire survey among the employees of the postal company, which gives the primary input data [57]. Application of HRSI model within the research itself consisted of the following steps: The questionnaire consists of three parts.…”
Section: Employee Job Satisfaction-methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these latent variables is determined by measurable variables (22). This model is based on the use of a questionnaire survey among the employees of the postal company, which gives the primary input data [57]. Application of HRSI model within the research itself consisted of the following steps: The questionnaire consists of three parts.…”
Section: Employee Job Satisfaction-methodologymentioning
confidence: 99%
“…Total satisfaction index values, calculated as the average of all indices, are expressed as a percentage. From these values, the overall value of the HRSI index was averaged [57].…”
Section: Calculation Of Hrsi Indexmentioning
confidence: 99%
“…Universitas [2]. Sejumlah negara Eropa telah mengembangkan indeks kepuasan pelanggan nasional untuk berbagai macam barang dan jasa.…”
Section: Pendahuluanunclassified
“…Customer satisfaction (Section 9.1.2 ISO 9001:2015) is one of the aspects related to the economic dimension of the set of identified sustainability variables (economic, environmental, and social). Strenitzerová et al [8] indicated that the success of customer satisfaction is closely related to a company's quality management and has a significant impact on the company's future and its customer-based corporate sustainability.…”
Section: Introductionmentioning
confidence: 99%